The Mechanism for Issuing Property Rights Certificates by the Land Office based on Village Letter C (Case Study at BPN Kendal Regency) - Afwan, Muhammad Bagus Satriyan; Bawono, Bambang Tri (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2023)
The state's recognition of land rights owned by legal subjects, which gives rise to control over land, makes the State obliged to guarantee legal certainty regarding land rights by registering land and issuing certificates as proof of land ownership. Before the certificate is issued, there is proof of ownership or control of land called a Copy of Letter C/Letter C, Girik, Petuk D or Kekitir. This research aims to: 1) determine and analyze the mechanism for issuing Ownership Certificates by the Kendal Regency Land Office based on Village letter C. 2) know and analyze the legal certainty of the Certificate of Ownership Rights based on Village letter C at the Kendal Regency BPN. This research uses an empirical juridical approach, namely by examining secondary data first and then continuing by conducting research on primary data in the field. Holders of certificates of land rights according to the law in force in Indonesia will have stronger rights claims, but the problem will not be that simple, because there is definitely the potential for land disputes. The process of issuing a certificate of ownership as strong evidence of ownership of land issued by the Kendal Regency Land Office is in accordance with applicable law in Indonesia. The results of the research show that the mechanism for issuing property rights certificates by the Kendal Regency Land Office, including systematic land registration for the first time through the National Agrarian Operations Project (Prona) through stages based on the laws and regulations in force in Indonesia , however, there are many requirements for the validity of a registration application. which was manipulated and indicated that there was an unlawful act. The legal certainty of the Certificate of Ownership issued by the Kendal Regency Land Office can still be contested. Heirs who object to the issuance of the certificate can file a lawsuit with the local court. The court will decide based on evidence that convinces the judge whether there is an unlawful act in issuing the certificate or confirming the issuance of the certificate.